Electrochemical reduction of aromatic sulfinic acids in dimethylsulfoxide - Angelo, ACD; Stradiotto, N. R. (Electrochemical Soc Inc, 1997)
The electrochemical reduction of benzenesulfinic, p-toluenesulfinic, and p-nitrobenzenesulfinic acids was studied in dimethylsulfoxide solutions. From cyclic voltammetry experiments, a chemical reaction following the first electron transfer was detected during the reduction process. A cyclic voltammetry technique using ultramicroelectrodes has provided kinetic parameters for the electron-transfer steps, from which it was possible to observe the influence of the ring substituent on the electrochemical reduction. The mechanism of the electroreduction of aromatic sulfinic acids in dimethylsulfoxide depends upon the nucleophilic attack of the radical anion produced on the starting compound during the reduction processes.